"Big Fish in a Small Pond": Chinese Migrant Shopkeepers in South Africa. (March 2014) - Lin, Edwin
The steady growth of Chinese migrants to South Africa in the past decade provides an opportunity to use Sen's (2001, Development as Freedom. Oxford: Oxford University Press) capabilities approach in the field of immigration. This theoretical framing reveals that the Chinese employ, what I call, a small pond migration strategy – utilizing mobility to maximize their social, economic, and human capital. I argue that the Chinese move to South Africa because of a desire to venture out of China and pursue freedoms associated with being one's own boss. Once in South Africa, they choose to stay because of comfortable weather and a slower pace of life, despite losing freedoms associated with high crime in Johannesburg. The findings suggest alternative ways of understanding factors of migration as well as a model that explains migration from more developed countries to less developed ones.